Cytochrome c as a Potentially Clinical Useful Marker of Mitochondrial and Cellular Damage - Eleftheriadis, Theodoros; Pissas, Georgios; Liakopoulos, Vassilios; Stefanidis, Ioannis (Frontiers in Immunology, 2016)
Mitochondria are evolutionary endosymbionts derived from bacteria. Thus they bear molecules, such as mitochondrial DNA that contains CpG DNA repeats and N-formyl peptides, found in bacteria. Upon cell necrosis or apoptosis these molecules are released into the interstitial space and the circulation and recognized by the immune cells through the same receptors that recognize pathogen associated molecular patterns, leading to inflammation. Other mitochondrial molecules are not of bacterial origin, but they may serve as danger associated molecular patterns (DAMPs) when due to cell injury are translocated into inappropriate compartments. There they are recognized by pattern recognition receptors of the immune cells. Cytochrome c is such a molecule. In this review experimental and clinical data are presented that confirms cytochrome c release into the extracellular space in pathological conditions characterized by cell death. This indicates that serum cytochrome c, which can be easily measured, may be a clinically useful marker for diagnosing and assessing the severity of such pathological entities. Reasonably, detection of high cytochrome c level into the circulation means release of various other molecules that serves as DAMPs when found extracellularly, the mitochondrial DNA and N-formyl peptides included. Finally, because the release of this universally found compound into the extracellular space makes cytochrome c an ideal molecule to play the role of a DAMP per se, the available experimental and clinical data that support such a role are provided.